Assessment of candidate genes and genetic heterogeneity in human non syndromic orofacial clefts specifically non syndromic cleft lip with or without palate. Issue 12 (December 2019) - Saleem, Komal; Zaib, Tahir; Sun, Wenjing; Fu, Songbin
Abstract: Non syndromic orofacial clefts specifically non-syndromic cleft lip/palate are one of the most common craniofacial malformation among birth defects in human having multifactorial etiology with an incidence of 1:700/1000. On the basis of association with other congenital malformations or their presence as isolated anomaly, OFC can be classified as syndromic (30%) and nonsyndromic (70%) respectively. The major cause of disease demonstrates complex interplay between genetic and environmental factors. The pathogenic mechanism of underlying factors have been provided by different genetic studies on large-scale with significant recent advances in genotyping technologies usually based on linkage or genome wide association studies (GWAS). On the basis of recent studies, new tools to identify causative genes involved in NSCL/P reported approximately more than 30 genetic risk loci that are responsible for pathogenesis of facial deformation. Despite these findings, it is still uncertain that how much of variance in NSCL/P predisposing factors can be explain by identified risk loci, as they all together accounts for only 20%–25% of NSCL/P heritability. So there is need of further findings about the problem of rare low frequency coding variants and other missing responsive factors or genetic modifiers. This review will described those potential genes and loci reported in different studies whose involvement in pathogenesis of nonsyndromic OFC has wide scientific evidence. Abstract : Cell biology; Genetics; Molecular biology; ; Developmental biology; Nonsyndromic orofacial clefts; Multifactorial; Heterogeneity; Cleft lip with or without palate.